Suppression of electron-transfer characteristics of ferrocene by OTS monolayer on a silicon/electrolyte interface - Kulkarni, S. A.; Kakade, Bhalchandra A.; Mulla, Imtiaz S.; Pillai, V. K. (Journal of Colloid and Interface Science, 2006)
The passivating behavior of self-assembled monolayers (SAMs) of octadecyltrichlorosilane (OTS) on an n-type Si(100) electrode with and without a redox species like ferrocene in a polar non-aqueous medium has been investigated using techniques like contact angle measurements, Fourier transform infrared (FTIR) spectroscopy and X-ray photoelectron spectroscopy (XPS) to understand the role of the monolayer. The electron-transfer behavior of ferrocene is found to be drastically affected by the presence of monolayer and the reasons for these are analyzed as a function of the change in resistance, dielectric thickness and coverage of the monolayer. Electrochemical impedance analysis in the presence of ferrocene gives the monolayer coverage as 0.998 and the apparent rate constant calculated from this gives 4.85 x 10(-12) cm s(-1) in comparison with 4.4 x 10(-8) cm s(-1) for a similar electrode without any monolayer. A positive shift of 200 mV in the flat-band potential after monolayer formation also suggests the covalent coupling of the silane nionolayer offering a protective barrier. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: cyclic voltammetry; ferrocene; impedance analysis; octadecyltrichlorosilane (OTS); rate constant; self-assembled monolayer (SAM)

Porous Co3O4 nanorods as superior electrode material for supercapacitors and rechargeable Li-ion batteries - Vijayanand, S.; Kannan, Ramaiyan; Potdar, H. S.; Pillai, V. K.; Joy, Pattayil Alias (Journal of Applied Electrochemistry, 2013)
Porous aggregated nanorods of Co3O4 with a surface area of similar to 100 m(2) g(-1) synthesized without using any templates or surfactants give very high specific capacitance of similar to 780 F g(-1) when used as electrode in a faradaic supercapacitor, with a cycle life of more than 1,000 cycles. Further, in Li-ion batteries when used as an anode, the Co3O4 nanorods achieved a capacity of 1155 mA h g(-1) in the first cycle and upon further cycling it is stabilized at 820 mA h g(-1) for more than 25 cycles. Detailed characterization indicated the stability of the material and the improved performance is attributed to the shorter Li-insertion/desertion pathways offered by the highly porous nanostructures. The environmentally benign and easily scalable method of synthesis of the porous Co3O4 nanorods coupled with the superior electrode characteristics in supercapacitors and Li-ion batteries provide efficient energy storage capabilities with promising applications.
Keywords: Cobalt oxide; Electrode materials; Li-ion battery; Porous nanostructures; supercapacitor